Gomery: prequel and sequel - Sutherland, S.L. (Revue Gouvernance / Governance Review, 2006)
The following text will first characterize the sponsorship scandal and then review the consequences for the shape of the inquiry created by its terms of reference. My view is that although the intent of establishing the inquiry was to demonstrate that all was well in an open democracy, the event itself, pulled out of the past, selectively refreshed grievance and outrage. The televized proceedings followed by daily headlines so inflamed the general public with the repetitive detailing of money losses that the public came to understand sponsorship’s root evil as only financial waste, and only Liberal Party corruption (« entitlement »). The inquiry as it was conducted thus forestalled more significant conversations that might have filled in between the criminal and civil trials. Worse, the inquiry created a view that the political corruption it emphasized, which it was at pains to emphasize as « artisan, » could have been almost casually forestalled at any point by ordinary levels of vigilance on the part of senior public servants. More specifically, the terms of reference either forced or normalized a selective approach to calling, questioning and recalling witnesses. Further, the judge the government of Prime Minister Paul Martin chose to lead the inquiry was the first to acknowledge that he lacked an understanding of responsible government, political institutions and public law. He therefore was swiftly provided with advisers on the political system and settled views he was in no position to know of or judge.